Arguments for preserving the sustainable heritage of colonial Algiers. - Daoudi, Nadia S. (Journal of North African Studies, 2021)
Due to climate change, we can no longer consider heritage objects as frozen curiosities from another time period, not even when they derive from the period of the French occupation (1830–1962). They are rather living objects – classified in UNESCO's terms as 'modern heritage' – which we inherited from our parents to pass on. Whether the heritage object is architecture or a landscape, its value can be defined according to its use. Practical environmental benefits can justify preserving an object as an example of 'sustainable heritage'. This essay analyses the value of a colonial-era atrium in downtown Algiers, dating from 1906, as well as of the Jardin d'Essai, a legendary Algiers garden.